Dysplastic gangliocytoma of the cerebellum in a cat. Issue 3 (May 2022) - Imlau, Michelle; Saeed, Mamoun; Cryan, Jane; Hoey, Seamus; McKenna, Myles; Jahns, Hanne; Kelly, Pamela
A 2.5-year-old cat presented with progressive ataxia and lethargy. Magnetic resonance imaging (MRI) showed enlargement of the cerebellum and herniation of cerebellar vermis. Postmortem examination confirmed the MRI findings, and histopathology showed numerous large dysplastic neurons populating and displacing the Purkinje cell layer and extending into the molecular and granular layers of the cerebellum. The lesion was diagnosed as dysplastic gangliocytoma of the cerebellum. In humans, this tumor is often associated with Cowden syndrome, a genetic disorder characterized by multiple hamartomas and an increased risk of developing certain neoplasms, known to be linked to a germline mutation of the phosphatase and tensin homolog ( PTEN ) gene. Reduction in PTEN nuclear and cytoplasmic immunohistochemical labeling of dysplastic neurons in this case suggested a possible PTEN mutation involved in the tumorigenesis. This report provides a detailed pathology description of the tumor and the use of neuronal and PTEN markers which will help guide pathologists presented with this rare condition in the future.